Neuropathic MORC2 mutations perturb GHKL ATPase dimerization dynamics and epigenetic silencing by multiple structural mechanisms - Douse, Christopher H.; Bloor, Stuart; Liu, Yangci; Shamin, Maria; Tchasovnikarova, Iva A.; Timms, Richard T.; Lehner, Paul J.; Modis, Yorgo (Nature communications, 2018)
Missense mutations in MORC2 cause neuropathies including spinal muscular atrophy and Charcot–Marie–Tooth disease. We recently identified MORC2 as an effector of epigenetic silencing by the human silencing hub (HUSH). Here we report the biochemical and cellular activities of MORC2 variants, alongside crystal structures of wild-type and neuropathic forms of a human MORC2 fragment comprising the GHKL-type ATPase module and CW-type zinc finger. This fragment dimerizes upon binding ATP and contains a hinged, functionally critical coiled-coil insertion absent in other GHKL ATPases. We find that dimerization and DNA binding of the MORC2 ATPase module transduce HUSH-dependent silencing. Disease mutations change the dynamics of dimerization by distinct structural mechanisms: destabilizing the ATPase-CW module, trapping the ATP lid, or perturbing the dimer interface. These defects lead to the modulation of HUSH function, thus providing a molecular basis for understanding MORC2-associated neuropathies. Microrchidia CW-type zinc finger protein 2 (MORC2) is an effector of epigenetic silencing by the human silencing hub (HUSH). Here the authors present the crystal structures of MORC2 and disease-causing MORC2 mutants and give mechanistic insights into how MORC2 mediates HUSH-dependent silencing.